Lack of Cross-Sector and Cross-Level Policy Coherence and Consistency Limits Urban Green Infrastructure Implementation in Malawi - Afionis, Stavros; Mkwambisi, David D.; Dallimer, Martin (Frontiers in Environmental Science, 2020)
The quality, quantity and accessibility of greenspaces and green infrastructure in urban areas offers multiple benefits for city dwellers, the environment and urban sustainability. Greenspaces provide a wide range of environmental, social, cultural, climate change adaptation and mitigation benefits. However, for urban greenspaces to do so, they need to be integrated into national policy and city-planning strategies in ways that recognise their value and importance. Consistency and coherence between policy sectors and levels is essential. The more prominent urban greenspaces are in national level policy, the easier it will be to ensure coherence and consistency between sectors and levels, as well as avoid national and local initiatives hindering each other’s effectiveness. Preserving and integrating urban greenspaces should be a priority for all cities, but even more so for Sub-Saharan African ones, which witness the fastest growing urban population among developing regions. Here we focus on Malawi, one of the most rapidly urbanising countries in the world. We collated and reviewed national-level and city-level policies and strategies, ranging from housing to transport and biodiversity, in order to determine whether urban greenspaces and green infrastructure have been incorporated into planning and management priorities. We found little evidence that urban greenspaces and green infrastructure are incorporated into national-level decision-making processes. In contrast, promoting and enhancing urban greenspace and infrastructure was a priority in planning and strategy documents produced by the Lilongwe and Mzuzu City Councils. Better institutional coordination and policy coherence across national level sectors that affect urban greenspaces and green infrastructure is required if their multiple benefits are to be realised.